The Impact of Pro-Environment Belief and Personal Norm toward the Beauty Purchase Behavior - Ikhsan, Ridho Bramulya; Br Sinukaban, Laranza Destami; Dinegoro, Radindya Citta; Annur, Rania Ramadhanty; Fernando, Yudi (Universitas Mercu Buana, 2023)
Objectives: The increasing use of eco-friendly beauty products in Indonesia attracts many researchers to understand buying behavior. Therefore, this study examines the effect of altruistic values, hedonic values, pro-environmental beliefs, personal norms, and independent decision-making on consumer buying behavior of eco-friendly beauty products.Methodology: This research is quantitative with an online survey of consumers purchasing green cosmetics products in Greater Jakarta, Indonesia. The determination of the number of samples is ten times the number of indicators with a purposive sampling technique. The research questionnaire was developed by several prior researchers who had been tested for validity and reliability. Structural equation modeling uses structural equation modeling-partial lease squares with SmartPLS software version 4 to test the research hypothesis.Finding: The results of the study show that altruistic values and hedonic values have a positive effect on pro-environmental beliefs. Furthermore, pro-environmental beliefs have a positive effect on personal norms. Finally, personal norms and independent judgment-making positively affect consumers' purchase behavior of green beauty products in Greater Jakarta.Conclusion: Green beauty purchase behavior in Greater Jakarta is influenced by personal norms and independent judgment-making which are also influenced by altruistic values, hedonic values, and pro-environmental beliefs. In the context of green beauty products, awareness that arises from within oneself can form a better level of consistency in buying green beauty product behavior. The findings from this study serve as a basis for managers and the Indonesian government to implement better eco-friendly strategies to motivate consumers to buy green products, especially cosmetics.